PROTOTYPE POMPA APUNG - SARITO SARITO; WARJIYO WARJIYO (Jurnal Poli-Teknologi, 2013)
ABSTRACT Floating pump is a water pump than can flat and adapt to the level of water surface. This water pump is solution of the problem happens because of the significant increase an decrease of the level of water. If this 125 watt water pump installed on the ground surface it is unable to suck water because the well water depth passes the maximum height of the water pump’s ability to suck water. If the water pump installed by hanging over the well, there is possibility of being soaked when the level of water surface increased. Working principal of the floating pump is based on the archimedes law, where every object that immerses in a liquid (water) will get a force to the top which valve is as big as the liquid removed by the object. Floater loaded by air install under the pump’s plate and support the weight of the floating pump system so that the system can float. The floating pump can be used and relatively stable of the shake of the machine pump and of the increase and decrease of the water level because it follows the increase and decrease velocity of the well water level. Flexible water pipe gives flexibility to the pump system to go up and down, following the water level. Height of the suction is not very high less than 20 cm and it is always constant because the pump system floating on the water surface. If it is compared by the maximum suction, 9 meters, it doesn’t affect the suction debit. Along with the level decrease of the pump system following the degradation of the well water level when the pump operated, there is a decrease in the debit because of the height increase of pushed pipe. Key words: floating pump, floater, water.